Socialization of the Independent Learning Curriculum for PJOK Teachers - Sumbara Hambali; Dhani A Zakaria; Yopi Meirizal; Sutiswo; Ruslan Rusmana (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The Joint Decree of the Four Ministers on Guidelines for The Implementation of Learning during the Covid-19 Pandemic requires that each education unit can carry out Limited Face-to-Face Learning (PTMT). However, recently the government has given each school the opportunity to determine the curriculum to be used by it, including the 2013 curriculum, emergency curriculum or independent curriculum. Especially in the independent curriculum, each school can implement it gradually according to their respective abilities. Therefore, each education unit must strive to be able to implement this independent curriculum, although still gradually. Based on these problems, as academics in the field of education, it is necessary to provide knowledge related to this independent learning curriculum, especially in PJOK subjects through the Community Service scheme. Therefore, the target of this socialization is PJOK teachers. The implementation method in this activity is delivery using the lecture method, discussion and question and answer, as well as task guidance in making PJOK learning strategies using an independent curriculum. The results of this activity are expected that PJOK teachers will be able to implement learning activities using an independent curriculum at every level of education or in their sects